Numerical simulation study of oil–water separation based on a super-hydrophilic copper net - Bai, Kun; Liu, Weinan; Zhao, Maoyu; Li, Kaifang; Tian, Yiming (Frontiers in Environmental Science, 2022)
Green and environmentally friendly oil–water separation is an important technique for reducing environmental pollution. In this study, the oil–water separation effect of the super-hydrophilic copper net was optimized through numerical simulation and orthogonal experiments. To be specific, a super-hydrophilic copper net was prepared using the solution etching method to perform oil–water separation experiments, and a favorable oil–water separation effect was achieved. First, the influences of oil–water flow velocity, copper net mesh size, and surface wettability on the oil–water separation effect of the super-hydrophilic copper net were explored via single-factor experiments. The results showed that the oil resistance of the super-hydrophilic copper net degraded, and its oil–water separation effect became poor due to the increasing oil–water flow velocity, enlarged copper net mesh size, and reduced oil contact angle on the surface of the super-hydrophilic copper net. On this basis, the optimized oil–water separation parameters were obtained through orthogonal experiments. The optimized process parameters were as follows: velocity = 0.1 m/s, copper net mesh size = 30 μm, oil contact angle = 150°, and oil removal rate = 95.7%. Furthermore, the copper net was etched using sodium hydroxide and sodium persulfate mixed solution to prepare a 500-mesh super-hydrophilic copper net for the oil–water separation experiment and then the oil removal rate reached 96.4%. The study results provide a theoretical basis, method, and means for the practical application of super-hydrophilic copper nets.